Progress in the Chemistry of Organic Natural Products 105 - Kinghorn, A. Douglas; Falk, Heinz; Gibbons, Simon; Kobayashi, Jun'ichi.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The first contribution reviews the occurrence of xanthine alkaloids in the plant kingdom and the elucidation of the caffeine biosynthesis pathway, providing details of the N-methyltransferases, belonging to the motif B' methyltransferase family which catalyze three steps in the four step pathway leading from xanthosine to caffeine. The second contribution in this book provides a background on the molecule and related compounds and update knowledge on the most recent advances in Iboga alkaloids. The third contribution presents a comprehensive analysis of frequently occurring errors with respect to 13C NMR spectroscopic data and proposes a straightforward protocol to eliminate a high percentage of the most obvious errors.
Xanthine Alkaloids: occurrence, biosynthesis, and function in plants -- The Iboga Alkaloids -- A critical evaluation of the quality of published 13C-NMR-Data in natural product chemistry.
Keywords: Chemistry, Organic; Pharmaceutical chemistry; Medicinal chemistry; Organic Chemistry; Pharmaceutics; Medicinal Chemistry